Incidence of Erosive Esophagitis in Patients of Gastroesophageal Reflux Disease - Raza Naqvi, Muhammad Abuzar; Khan, Javed Ahmad; Mehmood, Muhammad Amjad; Pirzada, Hijab Zainab; Bukhari, Syeda Kinza; Iqbal, Muhammad Mujahid (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the prevalence of erosive esophagitis among patients reported with gastroesophageal reflux disease at the outpatient department. Study Design: Prospective cross-sectional study. Place & duration of study: Department of Medicine, CMH, Multan from July 2024 to December 2024. Methods: A total of 120 patients aging ≥18 years presenting with the typical symptoms of gastroesophageal reflux (heartburn and/or acid regurgitation occurring at least twice weekly for ≥3 months) were included in this study. Upper gastrointestinal endoscopy was arranged for each patient and patients diagnosed with erosive esophagitis were graded as per the Los Angeles classification system. Descriptive statistics were used to summarize the demographic features, clinical features and the prevalence of erosive esophagitis among the study patients. Results: The mean age of participants was 42.05 ± 10.42 years (range: 26-62 years), with a slight male predominance (55.8% vs 44.2%). Endoscopic evaluation revealed the prevalence of erosive esophagitis as 21.7%, with the majority classified as Los Angeles grade A (10.8%), followed by grade B (5.8%), grade C (3.3%), and grade D (1.6%). The comparison of demographic characteristics revealed that the erosive esophagitis was significantly more prevalent in aging patients (p=0.001), male gender (p=0.045), higher BMI (p= ˂0.001), with smoking history (p=0.01) and patients reported with alcohol consumption (p=0.01). Similarly, patients having Hiatal hernia significantly suffered more from EE (p=0.04). The comparison between clinical symptoms among EE and Non-EE patients showed that symptoms like dysphagia (p=0.02) and night time reflux (p=0.04) were significantly higher in patients suffering EE compared to Non-EE patients. Conclusion: Nearly one-fifth of the patients reported with gastroesophageal reflux disease exhibit erosive esophagitis, with most cases classified as mild to moderate stage of the disease.